Complete genome sequence of Beutenbergia cavernae type strain (HKI 0122T). Issue 1 (July 2009) - Land, Miriam; Pukall, Rüdiger; Abt, Birte; Göker, Markus; Rohde, Manfred; Rio, Tijana; Tice, Hope; Copeland, Alex; Cheng, Jan-Fang; Lucas, Susan; Chen, Feng; Nolan, Matt; et al.
Abstract Beutenbergia cavernae (Grothet al. 1999) is the type species of the genus and is of phylogenetic interest because of its isolated location in the actinobacterial suborderMicrococcineae .B. cavernae HKI 0122T is a Gram-positive, non-motile, non-spore-forming bacterium isolated from a cave in Guangxi (China).B. cavernae grows best under aerobic conditions and shows a rod-coccus growth cycle. Its cell wall peptidoglycan contains the diagnostic L-lysine ← L-glutamate interpeptide bridge. Here we describe the features of this organism, together with the complete genome sequence, and annotation. This is the first completed genome sequence from the poorly populated micrococcineal familyBeutenbergiaceae, and this 4, 669, 183 bp long single replicon genome with its 4225 protein-coding and 53 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.